Chemical composition and in vitro antibacterial activity of essential oils from Murraya paniculata (L.) Jack (Rutaceae) ripe and unripe fruits against bacterial genera Mycobacterium and Streptococcus (Brazilian Journal of Pharmaceutical Sciences, 2020)
This study aims to investigate chemical composition of essential oils from Murraya paniculata (L.) Jack (Rutaceae) ripe and unripe fruits and determine their in vitro antibacterial activity. Essential oils were extracted by hydrodistillation from Murraya paniculata (L.) Jack ripe and unripe fruits collected in the Cerrado, in Rio Verde, southwestern Goiás, Brazil. They were analyzed by gas chromatography with flame ionization detector (GC-FID) and by gas chromatography-mass spectrometry (GC-MS). Sesquiterpenes, which represent the most abundant class of compounds in oils, predominated in both ripe and unripe fruits. Major constituents of essential oils extracted from ripe fruits (RF-EO) were β-caryophyllene (21.3%), α-ylangene (13.3%), germacrene-D (10.9%) and α-zingiberene (9.7%) whereas the ones of unripe fruits (UF-EO) were sesquithujene (25.0%), α-zingiberene (18.2%), germacrene-D (13.1%) and α-copaene (12.7%). In vitro antibacterial activity of essential oils was evaluated in terms of its minimum inhibitory concentration (MIC) values by the broth microdilution method in 96-well microplates. Both essential oils under investigation showed moderate anti-streptococcal activity against the following bacteria: Streptococcus mutans, S. mitis, S. sanguinis, S. sobrinus and S. salivarius. MIC values ranged between 100 and 400 µg/mL. Regarding the antimycobacterial activity, essential oils from M. paniculata (L.) Jack unripe and ripe fruits were active against Mycobacterium kansasii (MIC = 250 µg/mL), moderately active against M. tuberculosis (MIC = 500 µg/mL) and inactive against M. avium (MIC = 2000 µg/mL). This study was pioneer in revealing similar chemical profiles of both essential oils extracted from Murraya paniculata (L.) Jack unripe and ripe fruits, besides describing their in vitro anti-streptococcal and antimycobacterial activities.